The Impact of 9/11 on Psychology and Education - Morgan, M. author. aut Link
XXXI, 275 p. 5 illus.
Keywords: The Impact of 9-11 on Psychology and Education is the fifth volume of the six-volume series The Day that Changed Everything? edited by Matthew J. Morgan. It features forewords by Robert Sternberg and Philip Zimbardo.